Welfare Analysis with a Proxy Consumption Measure – Evidence from a Repeated Experiment in Indonesia - Menno Pradhan (Tinbergen Institute, 2001)
Every three years, Indonesia fields simultaneously two nationwide surveys which collect consumption data. Onecollects consumption using 23 questions, the other using 320 questions. Based on a repeated experiment inwhich the two questionnaires were randomly assigned across households, I examine the consequences of using ahigher level of aggregation in questioning. A mapping of distribution functions reveals the combined effect ofsystematic differences in measurement and measurement error. Using a pseudo cross-section approach, Ieliminate the effect of measurement error and find that using a high level of aggregation yields a lowerconsumption measure, and that the fraction of underestimation increases as consumption rises. A one percentincrease in average consumption increases the fraction by which consumption is underestimated by about .4percent point. Next, I examine the consequences of using the short consumption questionnaire in welfareanalysis. Higher relative measurement error in the consumption measure derived from the short questionnaireresults in higher poverty estimates even if the poverty line is adjusted to take account of the systematicunderestimation. Small differences are found for analysis that is based on the rank the individual holds in theconsumption distribution. In gradient analysis, it seems impossible to devise a simple correction factor for thehigher consumption elasticities that follow when the short questionnaire is used.
Keywords: 330; Measurement error; welfare analysis; consumption; Gesamtwirtschaftlicher Konsum; Lebensstandard; Wohlfahrtsanalyse; Indonesien